Retaining Health Activities Elementary School Teacher in Working Conditions in the Mountainous Region - Khallo, Oleksandra (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
This article describes how to create retaining health educational environment as a factor of performance intended life goals and objectives, its purpose and self-improvement. The notion educative and retaining health environment is analyzed. Active position illustrated subjective, based on an understanding of their health in a residence in the mountain environment .